The Effectiveness of Psychoeducation on Menstrual Disorders in Adolescent Girls: A Systematic Literature Review - Ima Sukmawati; Yuyun Rahayu; Rosmiati Rosmiati; Diny Nur Fauziyah; Ayu Endang Purwati; Rosidah Solihah; Neli Sunarni; Resna Litasari (LPPM STIKes Muhammadiyah Ciamis, 2025)
Introduction: Menstrual disorders such as dysmenorrhea and premenstrual syndrome (PMS) are common among adolescent girls and often cause physical discomfort and psychological distress that interfere with academic performance and daily functioning. Within the context of adolescent-centered health promotion, psychoeducation has been increasingly recognized as a non-pharmacological strategy to improve menstrual health and emotional well-being. Objective: This study aims to systematically review and synthesize evidence regarding the effectiveness of psychoeducational interventions in alleviating menstrual symptoms and improving psychological outcomes among adolescent girls. Specifically, it evaluates outcomes related to pain severity, premenstrual symptoms, emotional regulation, and illness perception. Method: A systematic search was conducted in PubMed, Google Scholar, ScienceDirect, Taylor & Francis, ProQuest, Wiley Online Library, JSTOR, SAGE Journals, and Springer Nature for randomized controlled trials (RCTs) published between 2015 and 2025. Eligible studies included adolescent girls aged 10–19 years who received psychoeducational interventions for menstrual disorders. The interventions varied in structure, duration, and theoretical basis, including models such as Leventhal’s Self-Regulation Model, Cognitive Behavioral Therapy (CBT), and psychodrama-based approaches. Study selection followed PRISMA 2020 guidelines.Methodological quality was appraised using the Critical Appraisal Skills Programme (CASP) checklist. Result: Five RCTs with a total of 395 participants met the inclusion criteria. The findings consistently demonstrated that psychoeducation significantly reduced menstrual pain severity and premenstrual symptoms while enhancing emotional regulation and illness perception. Most interventions were delivered in small-group formats across three to seven sessions, combining cognitive and behavioral components. Conclusion: Psychoeducation is an effective, feasible, and complementary intervention for managing menstrual disorders in adolescent girls. Integrating psychoeducational programs into school-based and primary healthcare settings can enhance adolescent reproductive health outcomes and promote holistic well-being through preventive and evidence-based approaches.